A keyword search algorithm for structured peer-to-peer networks. (1st January 2011) - Szekeres, Adriana; Baranga, Silviu Horia; Dobre, Ciprian; Cristea, Valentin
Peer-to-peer (P2P) networks are largely used for file-sharing and hence must provide efficient mechanisms for searching the files stored at various nodes. The existing structured P2P overlays support only 'exact-match' lookup which is hardly sufficient in a file-sharing network. This paper addresses the problem of keyword-based search in structured P2P networks. We propose a new keyword-based searching algorithm which can be implemented on top of any structured P2P overlay. We demonstrate that the proposed algorithm achieves very good searching results as it requires the minimum number of messages to be sent in order to find all the references to files containing at least the given set of keywords.